Engineering of CRISPR/Cas9‐mediated potyvirus resistance in transgene‐free Arabidopsis plants. (27th June 2016) - Pyott, Douglas E.; Sheehan, Emma; Molnar, Attila
Summary: Members of the eukaryotic translation initiation factor (eIF) gene family, including eIF4E and its paralogue eIF(iso)4E, have previously been identified as recessive resistance alleles against various potyviruses in a range of different hosts. However, the identification and introgression of these alleles into important crop species is often limited. In this study, we utilise CRISPR/Cas9 technology to introduce sequence‐specific deleterious point mutations at the eIF(iso)4E locus in Arabidopsis thaliana to successfully engineer complete resistance to Turnip mosaic virus (TuMV), a major pathogen in field‐grown vegetable crops. By segregating the induced mutation from the CRISPR/Cas9 transgene, we outline a framework for the production of heritable, homozygous mutations in the transgene‐free T2 generation in self‐pollinating species. Analysis of dry weights and flowering times for four independent T3 lines revealed no differences from wild‐type plants under standard growth conditions, suggesting that homozygous mutations in eIF(iso)4E do not affect plant vigour. Thus, the established CRISPR/Cas9 technology provides a new approach for the generation of Potyvirus resistance alleles in important crops without the use of persistent transgenes.